Interethnic contact in the context to gypsy minority in preadolescence - Sánchez-Muros Lozano, Patricia Sonsoles (Avances en Supervisión Educativa, 2016)
As part of an ethnographic study in public primary schools, in environments where majority and Roma minority have lived together for centuries, is explored in everyday discourse, the key factors of the social construction of the category, as well as early attitudes in the process of interethnic interaction in the classroom. The analysis of multiple data (discourse, proxemics classroom and sociometric networks) in a simple of 40 non-Roma students between 11-14 years old, in municipalities with high concentrations of Roma population, shows significant qualitative contrasts in ethnic prejudice. Categorizations, attitudes and processes of interethnic inclusion or exclusion are arbitrate by social factors that facilitate or reduced the development of ethnic prejudice in this critical learning period.